Influence of processing on starch digestibility and gut morphology in the weaned piglet - White, Gavin A. (2007)
To overcome the `post-weaning growth check' commonly seen at weaning, the incorporation of antibiotic growth promoters (AGPs) to the diet has been a useful management tool. Recent legislation within the European Union banning the use of AGPs at sub-therapeutic levels in animal feed means that the quality of dietary ingredients used in weaner diets has assumed a much more fundamental role. In order to improve the availability of starch in the piglet diet, processing of cereals is widely practised. However, descriptions of processing techniques used in many studies are simply referred to by name, with no regard of the precise variables used. In addition, many of the feed materials are simply referred to as `cooked' which gives little indication of nutritional value.